A Statistical Study of Water Resource Accounting in Ukraine in the Conditions of Martial Law - Motuzka, O. M. (Statistics of Ukraine, 2025)
The article contains results of a statistical study of water resource accounting in Ukraine in the conditions of martial law. The regulatory framework of water use is shown: constitutional principles and provisions of the Water Code of Ukraine, regulatory acts specifying accounting and monitoring schemes. A retrospective review of the evolution of the national water resource accounting system, from creation to transformation in the era of Ukraine’s independence, and gradual transition to the basin principle of management, was made.A description of the available water resources and their distribution across the Ukrainian territory is given, with underscoring the role of underground waters and water-shortage problems in southern and eastern regions of Ukraine. The operation of the water sector in the prewar period was analyzed, with outlining crucial changes occurring in the wartime. The dynamics of the total water intake, the structure of fresh water use by main economic sector, and the water discharge in surface water bodies was compared, enabling to reveal an express downward trend resulting from the ruining of infrastructures and stoppage of factories.The challenges faced by the accounting system in the wartime were elaborated on: missing data, losses of data on the occupied territories, disrupted operation of hydrological posts, laboratories, regular observations. Special emphasis was placed on the consequences of the ruining of Kakhovka water reservoir, entailing the stoppage of irrigation, change in hydrological regimes, increasing environmental and humanitarian risks.The official measures to eliminate the disastrous effects, especially capital investment in the renewal of sewage treatment plants, pumping stations, water pipes, and monitoring systems, are highlighted. The developments in statistical accounting of water resources in Ukraine were proposed: integration of satellite and GIS technologies, digitalization and creation of a single information system, consolidation of basin-based management, expansion of the regional observation networks, adaptation of techniques to emergency situations, and appropriate funding. Results of the study have practical value for public administration bodies, water-management organizations and the research community in the context of postwar recovery and water policy setting.